ChemInform Abstract: Transition‐Metal‐Mediated Synthesis of Trifluoroethyl Aryl Ethers. Issue 12 (March 2016) - Huang, Yangjie; Huang, Ronglu; Weng, Zhiqiang
Abstract: The copper(I)‐mediated reaction delivers trifluoroethyl, pentafluoropropyl‐, and tetrafluoropropylaryl‐, and a broad range of hetarylethers in generally high yields.